TRIANGULAR EMPLOYMENT RELATIONSHIP, EMPLOYMENT PRACTICES AND OPPORTUNITIES FOR CAREER GROWTH OF AGENCY WORKERS IN THE NIGERIAN BANKING INDUSTRY - Anyim, F. C.; Ideh, D. A. (UDS International Journal of Development, 2017)
The use of agency workers is a common phenomenon in the Nigerian banking industry. The study examines how employment practices and triangular employment relationship affect career opportunities of agency workers in the Nigerian banking industry. The study adopted a cross-sectional survey research design with the aid of a structured questionnaire and in-depth interview schedule. A total of 451 respondents were randomly selected from 18,451 agency workers in triangular employment relationship in the 4 selected banks. Data from the questionnaire were analyzed using both descriptive and inferential statistics, while the analysis of interview data was based on thematic analyses. The findings of the study revealed that: there is a significant relationship between employment practices and opportunities for career growth of agency workers in triangular employment relationship. The study therefore concludes that, triangular employment relationship does not enhance the agency workers’ opportunities for career growth as a result of their exposure to negative employment practices. Keywords: Agency, banking, career, employment, triangular